2023
DOI: 10.1002/jgh3.12902
|View full text |Cite
|
Sign up to set email alerts
|

Human gut microbiome: A primer for the clinician

Abstract: The human host gets tremendously influenced by a genetically and phenotypically distinct and heterogeneous constellation of microbial species—the human microbiome—the gut being one of the most densely populated and characterized site for these organisms. Microbiome science has advanced rapidly, technically with respect to the analytical methods and biologically with respect to its mechanistic influence in health and disease states. A clinician conducting a microbiome study should be aware of the nuances relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…The gut microbiome structure is affected by a variety of factors, including the environment, diet, age, and geographical location [ 2 , 3 , 4 , 5 , 6 ]. It has been suggested that the number of human cells in the human body may be fewer than its microbial cells and that the number of human genes may be 10–100 times less than what is found in the intestine of the host [ 1 , 7 , 8 , 9 ]. In the last few decades, the amount of research conducted on the influence of the gut microbiome on the host organism, in a field called microbiomics, has increased significantly [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome structure is affected by a variety of factors, including the environment, diet, age, and geographical location [ 2 , 3 , 4 , 5 , 6 ]. It has been suggested that the number of human cells in the human body may be fewer than its microbial cells and that the number of human genes may be 10–100 times less than what is found in the intestine of the host [ 1 , 7 , 8 , 9 ]. In the last few decades, the amount of research conducted on the influence of the gut microbiome on the host organism, in a field called microbiomics, has increased significantly [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiome comprises a large community of microorganisms (microbiota) and their collective genomes, metabolites, and proteins released in the gastrointestinal (GI) tract [1]. It is known that the generated products, such as short-chain fatty acids, interact with enteric mucosal host cells and influence physiological immune responses, protecting the host from infection and maintaining the function and morphology of intestinal epithelial cells [1,2]. The enteric microbiome includes different subsets, such as the virome (viruses), the mycobiome (fungi), the archaeome (archaea), and even some parasites, which diversify during individual growth [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%